Digital Government as Exponential Organization: New Technologies of Communication - D. R. Mukhametov (Мир новой экономики, 2022)
The article explores the exponential transformation of the digital government. Exponential organizations are the common model of management that characterized by the use of the informatized environment, third-party resources and digital platforms to scale processes and create new markets. The digital government is a complex of institutions for structuring social relations and conflicts in a network environment. The coupling of exponential organization and digital government models is realized through the focus on technologies of communication that allow the exchange and integration of surrounding knowledge into the system of management. The article presents the typology of technologies of communication with external and internal communities depending on the type of environment (internal/external) and options of access (inclusive/exclusive). The typology systematizes technologies of communication and demonstrates its capabilities for solving various tasks, including involving new agents in the field of public policy, organizing access to institutions, creating/extracting value, reducing the cost of information exchange between management structures. Technologies of communication allow the government to move to the policy of identifying and interacting with the diversity of the environment. The effects of the introduction of these technologies are evaluated on the example of Estonia. In conclusion, it is possible to consider the digital government as the exponential organization due to the information connectivity of the system, but it is difficult to unambiguously conclude the explosive growth of the value creation/extraction due to the functioning of the state as a non-equilibrium adaptive system.